Археологические исследования жилого дома в квартале LX в западной части Херсонесcкого городища в 2008 г. - Кленина, Е.Ю.; Бернацки, А.Б. (Археологічні дослідження в Україні, 2009)
Within the Ukrainian-Polish interdisciplinary long-term research project «Topography of Tauric Chersonesos» the archaeological research at the city-block LX in the western part of Chersonesos has been undertaken since 2004. It resulted in the discovery of two Byzantine period houses, each of 378 м2. Thus, a thesis about the poverty of the habitants of the western part of the city at least in Byzantine period is not valid. These dwelling structures are the largest of all discovered on the territory of Chersonesan site by the present time.